PEMBAGIAN KEWENANGAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN - Risal Risal; La Ode Munawir (Legal Standing : Jurnal Ilmu Hukum, 2021)
In the development of state administration after the second amendment to the 1945 Constitution of the Republic of Indonesia, it gave birth to Regional Heads who were elected democratically. In a democratic manner based on Law no. 23/2014, the regional head is elected directly by the people along with the deputy regional head. Regional Heads and Deputy Regional Heads carry out decentralized government affairs based on the powers they have as regulated in Article 65 and Article 66 of Law no. 23 of 2014 concerning Regional Government. This division of attribution authority is seen as one of the causes of conflict between the regional head and the deputy regional head in carrying out government affairs. Therefore, the division of authority for regional heads and deputy regional heads must be reviewed. In addition, the division of authority can also be done by way of delegation or mandate. The division of authority through delegation is stipulated by Regional Regulation (Article 13 Paragraph (2) letter b of Law No. 30 of 2014), while the distribution of authority through the mandate is stipulated by a Regional Head Decree (Article 66 Paragraph (2) of Law No. 23 of 2014).